Collaborative Problem Solving Based Learning A Literature Review In Selected Journals - Harjito Kusmanto; Woro Sumarni; Sri Wardhani; Wahyu Hardyanto; Putut Marwoto; Retno Sri Iswari (International Conference on Science, Education, and Technology, 2021)
The curriculum continues to develop along with the times. The rapid development of technology requires curriculum adjustments. The domain of knowledge is no longer the only core domain of the curriculum. The domains of skills, character, and meta learning play a role in successful learning. A learning model is needed that is able to activate the four curriculum components. One of them is a collaborative problem solving based learning model. How is this model implemented in science learning? Through this re search, the researcher tries to explore the related research results that have been reported in 5 selected journals.